RESOLUSI KONFLIK DI DUNIA ISLAM: ANTARA DAMAI, DIPLOMASI, DAN PERANG (PERSPEKTIF ISLAM DAN HUBUNGAN INTERNASIONAL) - Yulia Pradesi (UIN Sunan Kalijaga Yogyakarta, 2019)
In international relations, especially relations between countries, it will always have the potential to have cooperation, agreements, even disputes. In general, all countries in the world make relations between countries as a manifestation of wanting peace because every country definitely needs other countries to be able to meet their country's needs. The current concept of Diplomacy is something that international actors are currently doing to establish cooperation with a country. However, when the path of diplomacy cannot be used, using hard power in the form of war is an instinctive thing that is done by a country to achieve its interests. Islam has its own perspective and guidance in studying relations between countries, through peace, the concept of diplomacy and the circumstances in which war is permitted.Keywords: Peace-Diplomacy-War, Islamic Perspective, International Relations.